A TOPCon front SP silver paste and preparation method thereof
By designing a TOPCon front SP silver paste equipped with micron-scale physical method boronized high-silver powder and high-purity amorphous boron powder, the contact problem caused by the differences in the front main and fine grid glass systems of the TOPCon battery is solved, and efficient welding of electrodes and significantly improved battery efficiency is achieved.
Patent Information
- Application Number
- CN202411699868.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The glass systems of the front main gate and fine gate of TOPCon battery have large differences, resulting in strong composite and weak contact, significantly reducing Voc, FF and Eff. The difference in solid content of main and fine gate silver pastes leads to large contact resistance, reducing FF and Eff, and the wet weight of fine gate silver pastes is easily soldered and caused poor EL.
A TOPCon front SP silver paste is provided, and its formula includes 80-89 wt% silver powder, 1-10 wt% micron-scale physical method bored high silver powder, 7-12 wt% organic carrier, 0.1-2 wt% amorphous boron powder, 0.05-0.5 wt% polyacrylamide, 0.05-0.5 wt% polyethylene and 1.5-3.5 wt% glass powder for conductive paste. By adjusting the silver paste formula, it has the functions of both main gate and fine gate, reducing printing steps and improving the contact performance of the electrode.
The electrodes are achieved with high tension, low corrosion and high contact performance, which significantly improves Voc, FF and Eff, and avoids problems caused by differences in main and fine grid silver pastes.
Smart Images

Figure 2GI6XA15VUVFM4KIYQML00BGD5CYARZRDTY4HFJJ 
Figure WJNQ8RHKU15P7NSUYZCX6UO4OMA5OCO8RJCNKE7M
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to a TOPCon front SP silver paste and a preparation method thereof. Background Art
[0002] N-type TOPCon cells have developed rapidly in recent years, especially laser-assisted sintering technology (LIF), which has enabled TOPCon cells to achieve a new conversion efficiency. With the gradual increase in efficiency requirements, TOPCon front SP (Screen Printing) slurry has been put on the development agenda. Compared with the current fine grid + main grid DUP mode, SP slurry has a higher efficiency improvement trend.
[0003] Defects and shortcomings of the existing technology:
[0004] ① The glass systems of the main grid and fine grid on the front of the TOPCon battery are very different. The overlapping printing area of the main and fine grids is highly corrosive, forming a strong composite and weak contact, resulting in a significant reduction in Voc, FF and Eff.
[0005] ② Due to the difference in solid content between the main and fine grid silver pastes (the solid content of the fine grid is more than 6% higher than that of the main grid), the shrinkage rates are not synchronized, and the contact resistance between the two is very large, which reduces FF and Eff.
[0006] ③ As the wet weight of silver paste decreases, the fine grid is more likely to be broken during the component series soldering process, resulting in poor component EL. Summary of the invention
[0007] In view of the above technical problems, the present invention provides a TOPCon front SP silver paste and a preparation method thereof. The SP silver paste provided by the present invention can be adapted to the current LECO (Laser-enhanced contact optimization) process basis, reducing four printing steps to three printing steps, having a better component series soldering window, and a conversion efficiency improvement of more than 0.05% year-on-year.
[0008] To achieve the above object, the technical solution of the present invention is:
[0009] A TOPCon front SP silver paste, comprising, by weight, 80-89wt% silver powder, 1-10wt% micron-grade physically borated high silver powder, 7-12wt% organic carrier, 0.1-2wt% amorphous boron powder, 0.05-0.5wt% polyacrylamide, 0.05-0.5wt% polyethylene and 1.5-3.5wt% of the conductive paste glass powder;
[0010] The glass powder includes a main oxide and a functional oxide. Taking the glass powder as a measurement basis, the main oxide includes 5-30wt% of germanium dioxide, 0.5-20wt% of aluminum oxide, 0.5-80wt% of bismuth oxide and 0.5-30wt% of tellurium dioxide;
[0011] The functional oxides include 0-20wt% silicon oxide, 0-35wt% boron oxide, 0-10wt% gallium oxide, 0-20wt% lithium oxide or lithium carbonate, 0-20wt% barium oxide or barium carbonate, 0-20wt% calcium oxide, 0-20wt% zinc oxide, 0-20wt% titanium dioxide, 0-20wt% tungsten trioxide, 0-10wt% copper oxide, 0-10wt% manganese dioxide and 0-10wt% ferrous oxide, and the mass fractions of the functional oxides are not 0 at the same time, that is, the glass powder must contain the main oxide and the functional oxide.
[0012] Preferably, the Dmax of the boronized high silver powder is less than 6 μm, the Dmax of the amorphous boron powder is less than 6 μm, the D50 particle size of the glass powder is 0.8-2.0 μm, and the Dmax of the glass powder is less than 8 μm. Controlling the particle size of the glass powder can improve printability and is not prone to clogging the printing screen.
[0013] Preferably, the silver powder has a D50 particle size of 0.7-2.5 μm and a specific surface area of 0.3-1.5 m 2 / g, the tap density is 4.5-6.5g / mL, and the particle size of the silver powder is strictly controlled. If the particle size of the silver powder is too small, it is easy to agglomerate, which affects the dispersion in the organic carrier and causes the subsequent electrode conductivity to deteriorate. If the particle size of the silver powder is too large, the tensile force of the electrode will be poor.
[0014] Preferably, based on the SP silver paste, the organic vehicle comprises 1-10wt% of a binder, 0-5wt% of a first solvent, 0-2wt% of a thixotropic agent and 0-1wt% of a dispersant;
[0015] Based on the adhesive, the adhesive includes 5-70 wt % of a resin and 30-95 wt % of a second solvent.
[0016] Preferably, the resin is selected from any one or more of ethyl cellulose, acrylic resin, PVB (polyvinyl butyral), CAB (cellulose acetate butyrate), CAE (cellulose acetate), SEPS (styrene-ethylene / propylene-styrene block copolymer), SEBS (hydrogenated styrene-butadiene block copolymer), rosin resin, phenolic resin, epoxy resin, petroleum resin or acrylate;
[0017] The first solvent is selected from one or more of butyl carbitol, butyl carbitol acetate, terpineol, alcohol ester dodecanol, triethylene glycol butyl ether, TXIB (2,2,4-trimethyl-1,3-pentanediol diisobutyrate), diethylene glycol dibutyl ether or dimethyl adipate;
[0018] The second solvent is selected from one or more of butyl carbitol, butyl carbitol acetate, terpineol, alcohol ester dodecaol, triethylene glycol butyl ether, and TXIB;
[0019] The thixotropic agent is polyamide wax, and the dispersant is a fatty acid dispersant or a fatty amine dispersant, such as lauric acid, a fatty amine dispersant such as dodecylamine, or a fatty dispersant containing both carboxyl and amine groups, such as TDO.
[0020] Based on the same inventive concept, the present invention also provides a method for preparing a TOPCon front SP silver paste, comprising the following steps:
[0021] S1: Mixing polyacrylamide, polyethylene, amorphous boron powder and part of the organic carrier according to the SP silver paste ratio, so that the polyacrylamide and polyethylene are coated on the amorphous boron powder;
[0022] S2: According to the SP silver paste formula ratio, the remaining organic carrier, silver powder, high silver boride powder, glass powder and the product prepared in step S1 are mixed and stirred to obtain the TOPCon front SP silver paste.
[0023] Preferably, the preparation method of the glass powder is as follows: after mixing the glass powder formula evenly, the mixed glass powder is melted at 1100-1300°C for 0.5-1h, then annealed and cooled by a double-roll mill, and ball milled after cooling to control the glass powder D50 particle size to 0.8-2.0μm and the glass powder Dmax to <8μm; then dried and sieved to obtain the finished glass powder.
[0024] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:
[0025] 1. The special lead-free Ge-Al-Bi-Te glass system provided by the present invention can provide electrodes with high welding tensile force, low corrosion and high contact performance.
[0026] 2. The SP silver paste provided by the present invention adds micron-level physical borated high silver powder and high-purity amorphous boron powder, which further improves the contact performance of the electrode, and controls the Dmax of the borated high silver powder and the high-purity amorphous boron powder to be less than 6μm, thereby improving the contact performance of the electrode and controlling the amount of borated high silver to avoid affecting the sintering of the entire silver paste.
[0027] 3. In the present invention, polyacrylamide and polyethylene are added to the slurry. When the slurry is sintered at high temperature, the polyacrylamide decomposes to produce inert gas to inhibit the oxidation of elemental boron. Polyethylene decomposes in a high temperature environment to produce reducing gas, which can also inhibit the oxidation of elemental boron during high temperature sintering, thereby ensuring the activity of elemental boron.
[0028] The TOPCon front SP silver paste provided by the present invention has the functions of both fine grid paste and main grid paste, so that subsequent screen printing does not need to be divided into main grid printing and fine grid printing, and only one printing is required, thereby avoiding various problems caused by the difference between the main grid silver paste and the fine grid silver paste. DETAILED DESCRIPTION
[0029] It should be noted that in the metallization process of solar cells, fine grid silver paste and main grid silver paste play a vital role. The main function of the front fine grid silver paste is to collect the current on the surface of the cell and transmit it to the main grid line, while the main function of the main grid silver paste is to connect the fine grid, gather current, and assist welding.
[0030] Due to the large difference in the glass systems of the fine grid silver paste and the main grid silver paste on the front of the TOPCon battery, the overlapping printing area of the main and fine grids is highly corrosive, forming a strong composite and weak contact, which leads to a significant reduction in Voc, FF and Eff; the difference in solid content between the fine grid silver paste and the main grid silver paste and the asynchronous shrinkage rate result in a large contact resistance between the fine grid silver paste and the main grid silver paste, which reduces FF and Eff; as the wet weight of the silver paste decreases, the fine grid is more easily broken during the component string soldering process, resulting in poor component EL.
[0031] The present invention designs and adjusts the formula of silver paste so that the silver paste has the functions of both main grid silver paste and fine grid silver paste, so that the front side of the TOPCon battery only needs to be printed once, and there is no need to divide it into main grid printing and fine grid printing. Similarly, the silver paste does not need to be divided into main grid silver paste and fine grid silver paste, thereby avoiding the problems caused by the difference between the main grid and fine grid silver pastes.
[0032] The TOPCon front SP silver paste and the preparation method thereof proposed by the present invention are further described in detail below in conjunction with specific embodiments. The advantages and features of the present invention will become more apparent from the following description.
[0033] Example 1
[0034] TOPCon front fine grid silver paste includes silver powder, micron-level physical boronized high silver powder, glass powder, organic carrier, high-purity amorphous boron powder, polyacrylamide (PAM) and polyethylene (PE).
[0035] 1. Silver powder, high tap density monodisperse spherical silver powder, dosage 88.5wt%: silver powder D50 particle size is 1.5μm, specific surface area is 0.35m 2 / g, tap density 6.0g / mL.
[0036] 2. Micron-grade physical borated high silver powder, Dmax about 4.0μm, dosage 1.2wt%.
[0037] 3. Glass powder, dosage 1.8wt%, lead-free Ge-Al-Bi-Te system, totaling 100% by mass, including:
[0038] Main oxide: germanium dioxide 10wt%, aluminum oxide 5wt%, bismuth oxide 55wt%, tellurium dioxide 5wt%;
[0039] And functional oxides: silicon oxide 5wt%, boron oxide 10wt%, copper oxide 8wt%, and manganese dioxide 2wt%.
[0040] After the glass powder is prepared and mixed evenly, it is melted in a platinum crucible at 1140°C for 0.5 hours to make the glass liquid melt evenly and without residue; it is then annealed and cooled using a double-roll mill, and the obtained glass sheet is ball-milled to control the glass powder D50 particle size to 1.4μm and Dmax to about 7.5μm; it is then dried at 100°C and sieved through 150 mesh to obtain the finished glass powder.
[0041] 4. An organic carrier, with a usage of 8 wt %, comprising 1.5 wt % of a binder, 5 wt % of a first solvent, 1.2 wt % of a thixotropic agent, and 0.3 wt % of a dispersant.
[0042] The adhesive mainly comprises a resin and a second solvent, which are mixed, heated and stirred at a heating temperature of 80°C.
[0043] The weight of the resin in the adhesive is 40wt%, and the net content is 10wt% of ethyl cellulose, 25wt% of SEPS resin, and 5wt% of rosin resin.
[0044] The second solvent has a net content of 60 wt % of the adhesive and 50 wt % of butyl carbitol acetate and 10 wt % of carbitol acetate.
[0045] The first solvent is 2 wt % of butyl carbitol, 0.5 wt % of terpineol, 1.5 wt % of TXIB, and 1 wt % of dimethyl adipate.
[0046] Thixotropic agent: polyamide wax.
[0047] Dispersant: 0.2 wt% fatty acid dispersant and 0.1 wt% aliphatic dispersant containing both carboxyl and amine groups.
[0048] 5. High-purity amorphous boron powder, D50 is about 0.2μm, Dmax is about 3.0μm, and the mass ratio is 0.3wt%;
[0049] Add polyacrylamide (PAM) at a mass ratio of 0.1wt%;
[0050] Polyethylene (PE) was added at a mass ratio of 0.1wt%.
[0051] 6. Preparation method:
[0052] S1: 1.2wt% of the organic carrier, the above-mentioned high-purity amorphous boron powder, PAM and PE are first subjected to triple-roll grinding to coat the amorphous boron powder with PAM / PE;
[0053] S2: Mix the ingredients according to the formula ratio, stir and disperse the remaining organic carrier and other ingredients, grind them with three rollers, and sieve them to obtain TOPCon front SP silver paste A.
[0054] Example 2
[0055] TOPCon front fine grid silver paste includes silver powder, micron-level physical boronized high silver powder, glass powder, organic carrier, high-purity amorphous boron powder, polyacrylamide (PAM) and polyethylene (PE).
[0056] 1. Silver powder: 80wt% of high tap density monodisperse spherical silver powder: 70wt% of the silver powder has a particle size D50 of 1.8μm and a specific surface area of 0.25m 2 / g, tap density 6.4g / mL; 10wt% silver powder particle size D50 is 1.2μm, specific surface area 0.4m 2 / g, tap density 6.2g / mL;
[0057] 2. Micron-grade physical borated high silver powder, Dmax is about 5.5μm, dosage is 7wt%.
[0058] 3. Glass powder 3wt%: lead-free Ge-Al-Bi-Te system, the total mass ratio is 100wt%
[0059] Main oxide: germanium dioxide 25wt%, aluminum oxide 2wt%, bismuth oxide 15wt%, tellurium dioxide 18wt%;
[0060] And functional oxides: lithium carbonate 5wt%, titanium oxide 15wt%, zinc oxide 10wt%, gallium oxide 5wt%, tungsten oxide 5wt%.
[0061] After the glass powder is prepared and mixed evenly, it is melted in a platinum crucible at 1270°C for 1 hour to make the glass liquid melt evenly and without residue; it is then annealed and cooled using a double-roll mill, and the obtained glass sheet is ball-milled to control the glass powder D50 particle size to 1.0μm and Dmax to about 6.3μm; it is then dried at 100°C and sieved through 150 mesh to obtain a finished glass powder.
[0062] 4. An organic carrier of 9 wt %, including a binder of 2.5 wt %, a first solvent of 4 wt %, a thixotropic agent of 1.6 wt %, and a dispersant of 0.9 wt %.
[0063] The adhesive mainly consists of resin and solvent, which are mixed, heated and stirred at a heating temperature of 70°C.
[0064] The weight of the resin in the adhesive is 65wt%, and the net content is 10wt% of CAB resin, 10wt% of PVB resin, 25wt% of SEBS resin, and 20wt% of petroleum resin.
[0065] The weight of the second solvent in the adhesive is 35wt%, and the net content is 15wt% of triethylene glycol butyl ether, 15wt% of TXIB, and 5wt% of pineneol.
[0066] The first solvent: 1wt% of diethylene glycol dibutyl ether, 2wt% of alcohol ester, and 2wt% of triethylene glycol butyl ether.
[0067] Thixotropic agent: polyamide wax.
[0068] Dispersant 0.9wt%: 0.9wt% fatty amine dispersant.
[0069] 5. High-purity amorphous boron powder, D50 is about 0.5μm, Dmax is about 5.0μm, and the mass ratio is 0.6wt%; the mass ratio of added PAM is 0.2wt%; the mass ratio of added polyethylene is 0.2wt%.
[0070] 6. Preparation method:
[0071] S1: 2.4wtwt% of the organic carrier, the above-mentioned high-purity amorphous boron powder, PAM and PE are first subjected to triple-roll grinding to coat the amorphous boron powder with PAM / PE;
[0072] S2: Mix the ingredients according to the formula ratio, stir and disperse the remaining organic carrier and other ingredients, grind them with three rollers, and sieve them to obtain TOPCon front SP silver paste B.
[0073] Example 3
[0074] TOPCon front fine grid silver paste includes silver powder, micron-level physical boronized high silver powder, glass powder, organic carrier, high-purity amorphous boron powder, polyacrylamide (PAM) and polyethylene (PE).
[0075] 1. Silver powder: 85.5wt% of high tap density monodisperse spherical silver powder: 80wt% of the silver powder has a particle size D50 of 1.6μm and a specific surface area of 0.3m 2 / g, tap density 6.2g / mL; 5.5wt% silver powder particle size D50 is 0.8μm, specific surface area 0.5m 2 / g, tap density 5.5g / mL;
[0076] 2. Micron-grade physical borated high silver powder, Dmax is about 5.5μm, dosage is 3wt%.
[0077] 3. Glass powder 2.5wt%: Lead-free Ge-Al-Bi-Te system, the total mass ratio is 100wt% and the ratio is:
[0078] Main oxide: germanium dioxide 20wt%, aluminum oxide 15wt%, bismuth oxide 5wt%, tellurium dioxide 25wt%;
[0079] And functional oxides: boron oxide 5wt%, barium carbonate 10wt%, calcium oxide 15wt%, ferrous oxide 5wt%.
[0080] After the glass powder is prepared and mixed evenly, it is melted in a platinum crucible at 1200°C for 1 hour to make the glass liquid melt evenly and without residue; it is then annealed and cooled using a double-roll mill, and the obtained glass sheet is ball-milled to control the glass powder D50 particle size to 1.7μm and Dmax to about 7.4μm; it is then dried at 100°C and sieved through 150 mesh to obtain the finished glass powder.
[0081] 4. 8.5 wt % of an organic carrier, including 3.5 wt % of a binder, 4 wt % of a first solvent, 0.8 wt % of a thixotropic agent, and 0.2 wt % of a dispersant.
[0082] The adhesive mainly consists of resin and solvent, which are mixed, heated and stirred at a heating temperature of 70°C.
[0083] The weight of the resin in the adhesive is 30wt%, and the net content is 15wt% of ethyl cellulose resin, 10wt% of acrylic resin, and 5wt% of acrylate.
[0084] The weight of the second solvent in the adhesive is 70wt%, and the net content is 55wt% of alcohol ester and 15wt% of triethylene glycol butyl ether.
[0085] The first solvent: 2 wt % of dimethyl adipate and 2 wt % of butyl carbitol acetate.
[0086] Thixotropic agent: polyamide wax.
[0087] Dispersant 0.9wt%: 0.9wt% of an aliphatic dispersant containing both a carboxyl group and an amine group.
[0088] 5. High-purity amorphous boron powder, D50 is about 0.1μm, Dmax is about 2.0μm, and the mass ratio is 0.1wt%; the mass ratio of added PAM is 0.2wt%; the mass ratio of added polyethylene is 0.2wt%.
[0089] 6. Preparation method:
[0090] S1: 2.4wtwt% of the organic carrier, the above-mentioned high-purity amorphous boron powder, PAM and PE are first subjected to triple-roll grinding to coat the amorphous boron powder with PAM / PE;
[0091] S2 prepares the ingredients according to the formula ratio, and disperses the remaining organic carrier and other ingredients through stirring, three-roll grinding, and sieving to obtain TOPCon front SP silver paste C.
[0092] The formula ratios of the TOPCon front SP silver pastes of the above-mentioned Examples 1-3 are summarized in Table 1 below:
[0093] Table 1 TOPCon front SP silver paste formula ratio of Examples 1-3
[0094]
[0095] Table 1 shows the mass percentages.
[0096] The silver paste prepared above was used to print and sinter the fine grid + main grid two-time printing mode paste on the same production line under the same conditions. After the electrode was prepared, the voltage, current, fill factor, conversion efficiency and welding tension of the sample were measured. The results are shown in Table 2:
[0097] Table 2 Performance of electrodes obtained after sintering the slurries of Examples 1-3 and Comparative Example
[0098]
[0099] Note: BL is an electrode sample prepared by the slurry in the double printing mode of fine grid + main grid on the production line. The experimental data of sample AC is the difference between sample AC and sample BL.
[0100] This shows that the SP silver paste provided by the present invention does not need to be printed separately for fine grid and main grid, and only needs one printing to produce the electrode. Compared with the current electrode produced by printing fine grid + main grid twice, the voltage, fill factor and conversion efficiency are improved, and it also has welding tension. This shows that the SP silver paste provided by the present invention not only has the functions of fine grid silver paste and main grid silver paste, but also has better contact performance than the existing fine grid and main grid modes, thereby significantly improving Voc, FF and Eff.
[0101] The above is a detailed description of the implementation of the present invention in conjunction with specific embodiments, but the present invention is not limited to the above implementation. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.
Claims
1. A TOPCon front SP silver paste, characterized in that: The composition comprises 80-89wt% silver powder, 1-10wt% micron-grade physical boronized high silver powder, 7-12wt% organic carrier, 0.1-2wt% amorphous boron powder, 0.05-0.5wt% polyacrylamide, 0.05-0.5wt% polyethylene, and 1.5-3.5wt% glass powder by weight; The glass powder includes a main oxide and a functional oxide. Taking the glass powder as a measurement basis, the main oxide includes 5-30wt% of germanium dioxide, 0.5-20wt% of aluminum oxide, 0.5-80wt% of bismuth oxide and 0.5-30wt% of tellurium dioxide; The functional oxides include 0-20wt% silicon oxide, 0-35wt% boron oxide, 0-10wt% gallium oxide, 0-20wt% lithium oxide, 0-20wt% barium oxide, 0-20wt% calcium oxide, 0-20wt% zinc oxide, 0-20wt% titanium dioxide, 0-20wt% tungsten trioxide, 0-10wt% copper oxide, 0-10wt% manganese dioxide and 0-10wt% ferrous oxide, and the mass fractions of the functional oxides are not 0 at the same time.
2. The TOPCon front SP silver paste according to claim 1, characterized in that: The glass powder further comprises lithium carbonate and barium carbonate, wherein the lithium carbonate replaces lithium oxide, and the barium carbonate replaces barium oxide, and the mass fractions of the barium carbonate and lithium carbonate in the glass powder are both 0-20wt%.
3. The TOPCon front SP silver paste according to claim 1, characterized in that: The Dmax of the boronized high silver powder is less than 6 μm, the Dmax of the amorphous boron powder is less than 6 μm, the D50 particle size of the glass powder is 0.8-2.0 μm, and the Dmax of the glass powder is less than 8 μm.
4. The TOPCon front SP silver paste according to claim 1, characterized in that: The silver powder has a D50 particle size of 0.7-2.5 μm and a specific surface area of 0.3-1.5 m 2 / g, and the tap density is 4.5-6.5g / mL.
5. The TOPCon front SP silver paste according to claim 1, characterized in that: Taking the SP silver paste as a measurement basis, the organic vehicle includes 1-10wt% of a binder, 0-5wt% of a first solvent, 0-2wt% of a thixotropic agent and 0-1wt% of a dispersant; Based on the mass of the adhesive, the adhesive includes 5-70 wt % of a resin and 30-95 wt % of a second solvent.
6. The TOPCon front SP silver paste according to claim 5, characterized in that: The resin is selected from any one or more of ethyl cellulose, acrylic resin, PVB, CAB, SEPS resin, SEBS resin, rosin resin, phenolic resin, epoxy resin or petroleum resin; The first solvent is selected from one or more of butyl carbitol, butyl carbitol acetate, terpineol, alcohol ester dodecanol, triethylene glycol butyl ether, TXIB, diethylene glycol dibutyl ether or dimethyl adipate; The second solvent is selected from one or more of butyl carbitol, butyl carbitol acetate, terpineol, alcohol ester dodecaol, triethylene glycol butyl ether or TXIB; The thixotropic agent is polyamide wax, and the dispersant is a fatty acid dispersant or a fatty amine dispersant, or a fatty dispersant containing both a carboxyl group and an amine group.
7. A method for preparing TOPCon front SP silver paste according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Mixing polyacrylamide, polyethylene, amorphous boron powder and part of the organic carrier according to the SP silver paste ratio, so that the polyacrylamide and polyethylene are coated on the amorphous boron powder; S2: According to the SP silver paste formula ratio, the remaining organic carrier, silver powder, high silver boride powder, glass powder and the product prepared in step S1 are mixed and stirred to obtain the TOPCon front SP silver paste.
8. The method for preparing TOPCon front SP silver paste according to claim 7, characterized in that: The preparation method of the glass powder comprises the following steps: after mixing the glass powder formula evenly, melting the mixed glass powder at 1100-1300°C for 0.5-1h, annealing and cooling by a roller mill, ball milling after cooling, controlling the glass powder D50 particle size to be 0.8-2.0 μm and the glass powder Dmax to be less than 8 μm; and drying and sieving to obtain the finished glass powder.
Citation Information
Patent Citations
Lead-free composite glass adhesive solar battery positive silver paste
CN104979035A
Back silver paste
CN107068240A